Efeito de estímulos visuais e químicos do sexo oposto na reprodução da tilápia-do-Nilo - Castro, André Luis da Silva [UNESP] (2004)
Hypothalamic-Hypophysis-Gonad is the main neural-hormonal axis regulating fish reproduction. Such axis may be affected by male-female interactions stimulating physiological responses (as hormonal releasing and gonad development) and behavioral responses (as courtship, chasing and spawning) among the interacting animals. Thus, visual and chemical communication between opposite sex may modulate fish reproduction. This study checked the effect of visual and chemical male-female interaction in the Nile tilapia. Thus, fourteen couples were studied in four different conditions of communication: 1) only visual contact; 2) only chemical contact; 3) chemical and visual contact; 4) no sensorial contact (isolated). The reproductive behavior and gonad development were analyzed and compared among the conditions. The visual communication with the opposite sex raised the frequency of undulation (a courtship movement) in males and females, induced spawning in females and risen GSI in males. The chemical communication did not affect such parameters. It was concluded that the male-female visual communication is the main social stimulation factor on Nile tilapia reproduction